A combination of isolated phytochemicals and botanical extracts lowers diastolic blood pressure in a randomized controlled trial of hypertensive subjects - Biesinger, S; Michaels, H A; Quadros, A S; Qian, Y; Rabovsky, A B; Badger, R S; Jalili, T (European journal of clinical nutrition, 2016)
Background/Objectives: Isolated phytochemicals have been shown to reduce blood pressure; however, combinations of phytochemicals have rarely been tested in humans. We hypothesized that a combination of extracts from grape seed and skin (330 mg), green tea (100 mg), resveratrol (60 mg) and a blend of quercetin, ginkgo biloba and bilberry (60 mg) would reduce blood pressure (BP) in hypertensive subjects. Subjects/Methods: Eighteen individuals meeting BP requirements (⩾130 mm Hg systolic or ⩾85 mm Hg diastolic) and criteria for metabolic syndrome were enrolled in a double-blinded, placebo-controlled, crossover trial (ClinicalTrials.gov, NCT01106170). The 28-day placebo and supplement arms were separated by a 2-week washout period, and 14 -h daytime ambulatory BP was assessed at baseline and at the end point of each arm. Results: BP was not altered after placebo. After supplement treatment, diastolic pressure was reduced by 4.4 mm Hg ( P =0.024, 95% CI, 0.6–8.1), systolic pressure was unchanged and mean arterial pressure trended ( P =0.052) toward reduction. Serum angiotensin-converting enzyme activity was similar between placebo and supplement arms, but urinary nitrate and nitrite concentrations were significantly increased ( P =0.022) after supplementation. Human aortic endothelial cells treated with metabolites of the polyphenols used in the human supplement trial had a significant increase ( P =0.005) in insulin-stimulated eNOS phosphorylation and greater ( P <0.001) accumulation of nitrates/nitrites. Conclusions: Our clinical and in vitro data support the theory that this combination of polyphenols reduced diastolic pressure by potentiating eNOS activation and nitric oxide production. Such supplements may have clinical relevance as stand-alone or adjunct therapy to help reduce BP.